Remote Labs and Game-Based Learning for Process Control - Zaulkerman, Imran (2013)
Social networking platforms and computer games represent a natural informal learning environment for the current generation of learners in higher education. This paper explores the use of game-based learning in the context of an undergraduate chemical engineering remote laboratory. Specifically, students are allowed to manipulate chemical engineering equipment through their mobile phones. Two teams of students vie to manipulate the level of two tanks over a fixed period of time. Each team tries to stabilize their own tank and destabilize their opponent's tank. The key findings are that even though there were no statistically significant differences in the post-game performance between the control (the group that conducted a regular level-control experiment) and treatment (the group that played the remote laboratory level-control game) groups, the students did enjoy playing the game, found it addictive and believed that it enhanced their knowledge and understanding of control loops.